Acheiropodia: report on four new Brazilian patients - Fett-Conte, A. C. [UNESP]; Richieri-Costa, A. (Wiley, 1990)
We report on 4 new patients with acheiropodia (the handless and footless families of Brazil). This autosomal recessive condition involves all 4 limbs with a well-defined pattern of defects. Two of the patients described here had a small bone fragment in the upper stumps (Bohomoletz bone), an uncommon finding in acheiropodia.
Keywords: Acheiropodia; Limb congenital anomaly; Autosomal recessive inheritance; Consanguinity